Influences of Cost Factors Affecting Technical Performance of Local Government Projects in Nigeria: A Partial Least Square-Structural Equation Modeling (PLS-SEM) Approach - Gambo, Nuru; Said, Ilias; Ismail, Radzi (Penerbit Universiti Sains Malaysia, 2016)
The technical performance requirements of projects posed a challenge to the sustainable development of small size local government projects particularly in developing countries. Studies in the past focused mainly on the performance of major foreign construction firms mostly owned and operated by expatriates. Very few researches however, have been conducted to assess the relationship between major cost factors affecting technical performance of small size local government projects. This study is aimed at assessing the relationship between major cost factors that affect technical performance of small size local government projects in Nigeria. Survey instruments were administered to major stakeholders in the construction industry comprising of project clients, contractors and consultants using proportionate stratified random sampling method. A Warp partial least square-structural equation modeling (PLS-SEM) software algorithm was used for the analysis of collected data. The software is one of the powerful software for data analysis and has an advantage of providing p values based on the structure of the research model. The study concluded that cash flow problem, fraudulent practice and nature of construction environment are the major factors affecting technical performance of local government projects in Nigeria and further recommended the use of mediator variables like pay for performance and advance payment policy to minimise such negative effects. Governments in developing countries should devise a good cash flow policy and impose stringent penalties against any party involved in fraudulent activity